CONVECTIVE DRYING KINETICS OF YACON (Smallanthus sonchifolius Poepp. & Endl.) SLABS AND EVALUATION OF THE DRYER PID TEMPERATURE CONTROL SYSTEM - Baldeón, Edwin O.; Salas-Valerio , Walter F.; Vidaurre-Ruiz , Julio M.; Comettant-Rabanal , Raúl (Chilean Journal of Agricultural & Animal Sciences, 2024)
Yacon is a functional food that is rich in fructooligosaccharides (FOS) and highly perishable, which requires inexpensive methods for its preservation. Therefore, the research aimed to model the convective drying kinetics of yacon slabs and to evaluate the airflow effect using The Proportional-Integral-Derivative (PID) temperature controller. Different temperatures (60, 70, and 80 °C) at constant air velocity (0.87 m s-1) were evaluated in a convective tray drying system. Secondly, to determine the effect of air velocity on the PID temperature controller, different air velocities (0.81-2.06 m s-1) at constant temperature (70 °C) were studied. The results showed that Page's model was the best fitting of data obtained, the effective diffusivity of convective drying of yacon ranged from 1.22x10-10 to 1.9x10-10 m2 s-1 and the activation energy was 21.76 kJ mol-1. In addition, it was observed with PID temperature control that the best drying rate and lowest temperature signal error occurred at an air velocity of 1.46 m s-1, where the temperature signal was more stable and closer to the reference temperature. In conclusion, the kinetic modeling of the convective drying of yacon provides the optimal drying parameters and the behaviour of mass and heat transfer phenomena. Above all, considering that the effect of air velocity influences the drying kinetics and the PID temperature control of the dryer.